RAINBOW-COLORED IN NATURE: इन्द्रधनुष का सतरंगी स्वरुप - Gaekwad, Aasha (International Journal of Research -GRANTHAALAYAH, 2014)
Our nature is adorned with many colors. All the colors of the rainbow are spread in nature. Each color has its own different effect. With our favorite color, we can get complete information about the mentality of an individual world. The color of light - Why do we get different colors in the rainbow? This fact was discovered in 1665 by Newton. He had succeeded in getting his seven ingredients on the screen after passing through the prism of white light. When the sun passes through the prism of light, the seven-color group formed on the screen by the rays of the sun is called the spectrum of white light - purple, purple, blue, green, yellow, orange and red. This phenomenon of dividing the seven elements of white light into colors is called varna paranpana. हमारी प्रकृति अनेक रंग¨ से सजी हुई है। प्रकृति में फैल्¨ हुए सभी रंग इन्द्रधनुष अपने में समेटे हुए है। हर रंग का अपना अलग प्रभाव ह¨ता है। अपने मनपसंद रंग से किसी व्यंिक्त विष्¨ष की मानसिकता की जानकारी हम पूर्ण रुप से प्राप्त कर सकते हैं । प्रकाष का वर्ण विक्ष्¨पण -इन्द्रधनुष में विभिन्न रंग हमे क्य¨ं प्राप्त ह¨ते है इस तथ्य की ख¨ज सन 1665 में न्यूटन द्वारा की गई थी। उन्ह¨ने ष्वेत प्रकाष क¨ प्रिज्म से गुजारने पर उसके सात अवयवी रंग¨ क¨ परदे पर प्राप्त करने में सफलता प्राप्त की थी। सूर्य के प्रकाष क¨ प्रिज्म में से गुजारने पर निर्गत किरण¨ं द्वारा परदे पर बनाये सात रंग¨ के समूह क¨ ष्वेत प्रकाष का वर्णक्रम कहते हैं - बैंगनी, जामुनी, नीला, हरा, पीला, नारंगी अ©र लाल रंग। ष्वेत प्रकाष के सात अवयवी रंग¨ में विभक्त ह¨ने की इस घटना क¨ वर्ण विक्ष्¨पण कहते है।